OTENTISITAS REKONTRUKSI HISTORIS TRANSFORMASI HUKUM WARIS ISLAM DAVID S. POWERS - Aisah, Aisah; Sukardi, Imam (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
The authenticity of the Quran and Sunnah is a controversial issue among Islamic studies scholars, and the answer to this question is a complex topic related to religious sensitivity. David Powers' research on the authenticity of the Islamic law of inheritance in his work "Studies in Qur'an and Hadith: The Formulation of the Islamic Law of Inheritance" is a fact that needs to be re-examined by investigating Powers' literature and thoughts, both pro and contra, from insiders and outsiders. Powers found differences between the law of inheritance accepted by Muhammad (Proto Islamic Law) and the Islamic Law of Inheritance. He expressed his disbelief in the sources of Islamic tradition in criticizing the interpretations of early generations. He even harshly criticized the supporting sciences of interpretation, such as the science of mansukh naskh, the science of qirā'āt, and asbāb al-nuzūl. According to him, these sciences were used to manipulate interpretations that should have been the interpretations they adopted under certain political conditions in early Islam. This article focuses on the authenticity of the historical reconstruction of the transformation of Islamic inheritance law in Powers' work, especially Proto Islamic Law and Islamic Law of Inheritance.